High-Tolerance Grating Couplers for Vertical Backside Coupling - Jui-Hung Chen; Arthur D. Bouamra; Chia-Ling Wu; Andrea Fiore; Shuo-Yen Tseng (Applied Sciences)
To facilitate convenient packaging of photonic integrated circuits on a fiber tip, a silicon grating coupler designed for vertical backside coupling has been developed. In order to comply with foundry capabilities and streamline the fabrication processes, the grating coupler features a minimum feature size larger than 200 nm and a single-etched structure on silicon. By inverse design-based optimization, the vertical backside grating coupler achieves a coupling efficiency of nearly 40% (−3.97 dB), while showcasing high fabrication and misalignment tolerance.